Hydrolysis-resistant polycarbonate compositions

CN116096818BActive Publication Date: 2026-10-23COVESTRO DEUTSCHLAND AG
View PDF 27 Cites 0 Cited by

Patent Information

Application Number
CN202180053120.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-08-31
Filing Date
2021-08-26
Publication Date
2026-10-23
Estimated Expiration
2041-08-26

AI Technical Summary

Technical Problem

[0007]但是,具有UL94 V-0性能的市售阻燃聚碳酸酯组合物在70℃的热水中浸泡7天后无法实现V-0性能,且因此对室外应用并不理想

Benefits of technology

[0265]由上文例举的根据本发明的实施例可以得出结论,根据本发明的组合物具有耐水解性、阻燃性和甚至在低温下也良好的耐冲击性的组合。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004097195950000051
    Figure BDA0004097195950000051
  • Figure BDA0004097195950000052
    Figure BDA0004097195950000052
  • Figure BDA0004097195950000061
    Figure BDA0004097195950000061
Patent Text Reader

Abstract

The present invention relates to a polycarbonate composition comprising the following components: A) 80 to 97.5 parts by weight of an aromatic polycarbonate; B) 0.1 to 0.3 parts by weight of a metal organosulfonate; C) 0.3 to 0.7 parts by weight of an anti-dripping agent; D) 0.1 to 4 parts by weight of a hydrolysis stabilizer; and E) 2 to 7 parts by weight of a polysilsesquioxane, wherein the total amount of the composition is 100 parts by weight. The present invention also relates to shaped articles made from the composition. The polycarbonate composition according to the present invention has a good combination of hydrolysis resistance and flame retardancy.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to hydrolysis-resistant polycarbonate (PC) compositions and molded articles made therefrom. Background Technology

[0002] Polycarbonate resin compositions possess excellent mechanical and electrical properties, such as dielectric strength, surface / volume resistivity, and dielectric constant, and are commonly used in automotive applications as well as in electronic and electrical equipment applications. Efforts have been made to develop polycarbonate compositions that meet the requirements of a wide range of applications.

[0003] US8927636B2 discloses a method for achieving good flame retardancy, impact resistance and surface quality by incorporating organometallic sulfonates, fluoropolymers, specified silsesquioxane particles and specified graft copolymers into polycarbonate resins.

[0004] US6518357B discloses formulations that achieve UL94 V-0 at 1 / 8-inch and 1 / 16-inch thicknesses, obtained by blending polycarbonate with three different siloxane additives: poly(phenylmethylsiloxane), (phenylsilsesquioxane)-co-(dimethylsiloxane), and poly(phenylvinylsilsesquioxane).

[0005] JP4890766 B2 discloses a light-diffusing aromatic polycarbonate resin composition in which special polyorganosilsesquioxane particles (which have a weight loss of 1% at 400-500°C in the (TGA) thermogravimetric method according to (B) JIS K7120) are used as light diffusers and added to the polycarbonate. The light-diffusing aromatic polycarbonate resin composition exhibits high brightness when used in direct-lit backlight diffusers.

[0006] There are many requirements for plastic housing materials used in outdoor applications facing harsh conditions such as extreme high or low temperatures, high humidity, and fire risks. For outdoor applications of electronic and electrical equipment (EE&A), plastic housing materials are required to have good flame retardancy and excellent hydrolytic resistance. Excellent hydrolytic resistance certification requires the material to maintain its flame retardant properties after being immersed in hot water at 70°C for 7 days.

[0007] However, commercially available flame-retardant polycarbonate compositions with UL94 V-0 performance cannot achieve V-0 performance after being immersed in hot water at 70°C for 7 days, and are therefore not ideal for outdoor applications.

[0008] Therefore, it is still necessary to have a polycarbonate composition with V-0 performance and good hydrolysis resistance according to UL94, which means that a 1.2 mm thick article made from it can also achieve V-0 performance after being immersed in hot water at 70°C for 7 days. Invention Overview

[0010] One object of this application is therefore to provide a polycarbonate composition having a good combination of hydrolysis resistance and flame retardancy, wherein articles made therefrom with a thickness of 1.2 mm can achieve V-0 performance before and after immersion in hot water at 70°C for 7 days.

[0011] According to the present invention, when an article made of the composition with a thickness of 1.2 mm achieves V-0 performance before and after immersion in hot water at 70°C for 7 days, the composition exhibits good hydrolysis resistance.

[0012] Surprisingly, this problem is solved by a polycarbonate composition comprising the following components:

[0013] A) 80-97.5 parts by weight of aromatic polycarbonate;

[0014] B) 0.1-0.3 parts by weight of organometallic sulfonates;

[0015] C) 0.3-0.7 parts by weight of anti-drip agent;

[0016] D) 0.1-4 parts by weight of hydrolysis stabilizer; and

[0017] E) 2-7 parts by weight of polysilsesquioxane

[0018] The total amount of the composition is 100 parts by weight.

[0019] A further object of the present invention is a molded article made from the polycarbonate composition according to the present invention.

[0020] Another object of the present invention is a method for preparing the above-described molded articles, comprising injection molding, extrusion molding, blow molding or thermoforming of the polycarbonate composition according to the present invention.

[0021] Another object of the present invention is the use of polysilsesquioxane as a hydrolysis resistance enhancer in a polycarbonate composition comprising at least one hydrolysis stabilizer, wherein the amount of polysilsesquioxane is 2-7 parts by weight based on a total amount of 100 parts by weight of the polycarbonate composition, and wherein the hydrolysis resistance enhancer is understood to be a component that, together with the hydrolysis stabilizer, brings about hydrolysis resistance as defined above.

[0022] The polycarbonate composition according to the present invention has a good combination of hydrolysis resistance and flame retardancy.

[0023] The polycarbonate composition according to the invention achieves a V-0 rating as measured according to UL94:2015 even at low thicknesses, such as 1.2 mm, after immersion in water at 70°C for 7 days.

[0024] Other subjects, features, aspects, and advantages of the invention will become clearer when reading the following description and examples. Invention Details

[0026] In the following text and unless otherwise specified, the limits of the numerical range are included within this range, especially in the terms “between” and “from”.

[0027] Throughout this application, the term "comprising" is interpreted as encompassing all specifically mentioned features as well as optional, additional, or unspecified features.

[0028] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains. Where the definitions of terms in this specification conflict with the meanings commonly understood by one of ordinary skill in the art to which this invention pertains, the definitions set forth herein shall prevail.

[0029] Unless otherwise specified, all numerical values ​​used in the specification and claims to indicate quantities of ingredients, etc., shall be understood to be modified by the term “about”.

[0030] Component A

[0031] The polycarbonate composition according to the present invention comprises an aromatic polycarbonate as component A. The aromatic polycarbonate may be a mixture of one or more aromatic polycarbonates.

[0032] According to the present invention, "aromatic polycarbonate" or simply "polycarbonate" should be understood to include both aromatic homopolymers and copolymers, including polyesters, wherein the polycarbonate may be linear or branched in a familiar manner. Mixtures may also be used.

[0033] In the polycarbonate used according to the invention, a portion (up to 80 mol%, preferably 20 mol% to 50 mol%) of the carbonate groups may be replaced by aromatic dicarboxylic acid ester groups. Such polycarbonates, incorporating both acid groups from carbonic acid and acid groups from aromatic dicarboxylic acids into the molecular chain, are referred to as aromatic polyester carbonates. In the context of this invention, they are covered by the comprehensive term "thermoplastic aromatic polycarbonate".

[0034] The substitution of carbonate groups for aromatic dicarboxylic acid ester groups is carried out stoichiometrically and quantitatively so that the molar ratio of reaction partners is also visible in the final polyester carbonate. The incorporation of dicarboxylic acid ester groups and their placement within blocks can be statistical.

[0035] Thermoplastic polycarbonate, including thermoplastic aromatic polyester carbonate, having a weight-average molecular weight M of 10,000 g / mol to 35,000 g / mol, preferably 12,000 g / mol to 32,000 g / mol, more preferably 15,000 g / mol to 32,000 g / mol, and particularly 20,000 g / mol to 31,500 g / mol. w Determined by gel permeation chromatography using CH2Cl2 as a diluent, calibrated with a standard (from PSS Polymer StandardsService GmbH, Germany) of known molecular weight distribution (made from bisphenol A and phosgene), according to method 2301-0257502-09D from Currenta GmbH & Co. OHG, Leverkusen (from the 2009 German version). Diluent: dichloromethane. Column assembly from cross-linked styrene-divinylbenzene resin. Analytical column diameter: 7.5 mm, length: 300 mm. Column material particle size: 3 μm to 20 μm. Solution concentration: 0.2 wt%. Flow rate: 1.0 mL / min, solution temperature: 30 °C. Detected using a refractive index (RI) detector.

[0036] Details about the preparation of polycarbonate have been disclosed in numerous patent documents over the last 40 years. See Schnell, "Chemistry and Physics of Polycarbonates", Polymer Reviews, Vol. 9, Interscience Publishers, New York, London, Sydney, 1964; D. Freitag, U. Grigo, PRMüller, H. Nouvertné, BAYER AG, "Polycarbonates" in Encyclopedia of Polymer Science and Engineering, Vol. 11, 2nd edition, 1988, pp. 648-718; and finally, U. Grigo, K. Kirchner, and PRMüller, "Polycarbonate" in Becker / Braun, Kunststoff-Handbuch [Plastics handbook], Vol. 3 / 1, Polycarbonate, Polyacetal, Polyester, Celluloseester [Polycarbonates, Polyacetals, Polyesters, Celluloseesters], Carl Hanser Verlag Munich, Vienna 1992, pp. 117-299.

[0037] Preferred methods for producing polycarbonates, including polyester carbonates, according to the present invention are the interfacial process and the melt transesterification process (e.g., WO 2004 / 063249 A1, WO 2001 / 05866 A1, WO 2000 / 105867, US 5,340,905 A, US 5,097,002 A, US-A 5,717,057 A).

[0038] Aromatic polycarbonates are prepared, for example, by an interfacial reaction of a dihydroxyaryl compound with a carbonyl halogen, preferably phosgene, and / or with an aromatic dicarbonyl dihalogen, preferably a phenyl dicarbonyl dihalogen, optionally using a chain terminator and optionally a trifunctional or greater branching agent. In the production of polyester carbonates, a portion of the carbonate derivative is replaced by an aromatic dicarboxylic acid or a derivative of a dicarboxylic acid, i.e., the carbonate structural unit in the aromatic polycarbonate is replaced by a dicarboxylic acid ester structural unit. They can also be prepared by melt polymerization via a reaction of a dihydroxyaryl compound with, for example, diphenyl carbonate.

[0039] The dihydroxyaryl compounds suitable for preparing polycarbonates are those of formula (1).

[0040] HO-Z-OH (1),

[0041] in

[0042] Z is an aromatic group having 6 to 30 carbon atoms and may contain one or more aromatic rings, which may be substituted and may contain aliphatic or alicyclic groups or alkylaryl or heteroatoms as bridging elements.

[0043] Preferably, Z in formula (1) is a group of formula (2).

[0044]

[0045] in

[0046] R 6 and R 7 Each independently consists of H, Cl- to C 18 -alkyl, C1-to-C 18 -alkoxy, halogen such as Cl or Br, or optionally substituted aryl or aralkyl in each case, preferably H or C1- to C1-. 12 -alkyl, more preferably H or C1- to C8-alkyl, and most preferably H or methyl, and

[0047] X is a single bond, -SO2-, -CO-, -O-, -S-, C1- to C6-alkylene, C2- to C5-alkylidene, or C5- to C6-cycloalkylidene, which may be substituted with a C1- to C6-alkyl group, preferably methyl or ethyl, or optionally fused to another heteroatom-containing aromatic ring. 12 -Aspartic acid.

[0048] Preferably, X is a single bond, C1- to C5-alkylene, C2- to C5-alkylidene, C5- to C6-cycloalkylidene, -O-, -SO-, -CO-, -S-, or -SO2-.

[0049] or groups of formula (2a)

[0050]

[0051] Examples of dihydroxyaryl compounds suitable for preparing polycarbonates according to the present invention include hydroquinone, resorcinol, dihydroxydiphenyl, bis(hydroxyphenyl)alkanes, bis(hydroxyphenyl)cycloalkanes, bis(hydroxyphenyl)sulfides, bis(hydroxyphenyl) ethers, bis(hydroxyphenyl) ketones, bis(hydroxyphenyl) sulfones, bis(hydroxyphenyl) sulfoxides, α,α′-bis(hydroxyphenyl)diisopropylbenzene, and their alkylated, cyclo-alkylated, and cyclo-halogenated compounds.

[0052] Preferred dihydroxyaryl compounds are 4,4′-dihydroxybiphenyl, 2,2-bis(4-hydroxyphenyl)propane (bisphenol A), 2,4-bis(4-hydroxyphenyl)-2-methylbutane, dimethylbisphenol A, 1,1-bis(4-hydroxyphenyl)-p-diisopropylbenzene, 2,2-bis(3-methyl-4-hydroxyphenyl)propane, 2,2-bis(3-methyl-4-hydroxyphenyl)propane, bis(3,5-dimethyl-4- 2,2-Bis(3,5-dimethyl-4-hydroxyphenyl)methane, bis(3,5-dimethyl-4-hydroxyphenyl)propane, bis(3,5-dimethyl-4-hydroxyphenyl)sulfone, 2,4-bis(3,5-dimethyl-4-hydroxyphenyl)-2-methylbutane, 1,1-bis(3,5-dimethyl-4-hydroxyphenyl)-p-diisopropylbenzene and 1,1-bis(4-hydroxyphenyl)-3,3,5-trimethylcyclohexane, and bisphenols (I) to (III).

[0053]

[0054] In each case, R' is a C1- to C4-alkyl, aralkyl, or aryl, preferably methyl or phenyl, with methyl being the most preferred.

[0055] Particularly preferred dihydroxyaryl compounds are 2,2-bis(4-hydroxyphenyl)propane (bisphenol A), 2,2-bis(3,5-dimethyl-4-hydroxyphenyl)propane, 1,1-bis(4-hydroxyphenyl)cyclohexane and 1,1-bis(4-hydroxyphenyl)-3,3,5-trimethylcyclohexane (bisphenol TMC) and dimethylbisphenol A, as well as dihydroxyaryl compounds of formulas (I), (II) and (III).

[0056] For example, in US 2,999,835 A, 3,148,172 A, 2,991,273 A, 3,271,367 A, 4,982,014 A, and 2,999,846 A; German Publications 1,570,703 A, 2,063,050 A, 2,036,052 A, 2,211,956 A, and 3,832,396 A; French Patent Application 1,561,518 A1; monographs “H. Schnell, Chemistry and Physics of Polycarbonates, Interscience Publishers, New York 1964, pp. 28 and thereafter; pp. 102 and thereafter” and “D. Glegrand, J. T. Bendler, Handbook of Polycarbonate Science and Technology, Marcel Dekker, New York”. These and other suitable dihydroxyaryl compounds are described in "2000, page 72 and thereafter".

[0057] In the case of homopolymer carbonates, only one dihydroxyaryl compound is used; in the case of copolymer carbonates, two or more dihydroxyaryl compounds may be used. The dihydroxyaryl compounds used—and the components of the compositions according to the invention—are similar to all other chemicals and auxiliaries added to the synthesis and may be contaminated by contaminants from their own synthesis, handling, and storage. However, it is most desirable to use raw materials of the highest possible purity.

[0058] The copolycarbonate of component A according to the present invention can also be prepared using 1 to 25% by weight (based on the total amount of bisphenol used), preferably 2.5 to 25% by weight, of a polydiorganosiloxane having hydroxyl aryloxy end groups. These are known and can be prepared by methods known in the literature (see, for example, US 3,419,634). Copolycarbonates containing polydiorganosiloxanes are also suitable; for example, the preparation of copolycarbonates containing polydiorganosiloxanes is described in DE-A 3,334,782.

[0059] Examples of suitable carbonate derivatives include phosgene or diphenyl carbonate.

[0060] Suitable chain terminators for the production of polycarbonate are monophenols. Suitable monophenols are, for example, phenol itself, alkylphenols such as cresol, p-tert-butylphenol, cumylphenol, and mixtures thereof.

[0061] Preferred chain terminators are straight-chain or branched C1- to C2-chain terminators. 30-Alkyl mono- or poly-substituted phenols, preferably unsubstituted or tert-butyl substituted. Particularly preferred chain terminators are phenol, cumylphenol and / or p-tert-butylphenol.

[0062] The amount of chain terminator used is preferably 0.1 to 5 mol% based on the molar number of the dihydroxyaryl compound used in each case. The chain terminator can be added before, during, or after the reaction with the carbonate derivative.

[0063] Suitable branching agents are trifunctional or more functional compounds familiar in polycarbonate chemistry, especially those with three or more phenolic OH groups.

[0064] Examples of suitable branching agents include 1,3,5-tris(4-hydroxyphenyl)benzene, 1,1,1-tris(4-hydroxyphenyl)ethane, tris(4-hydroxyphenyl)phenylmethane, 2,4-bis(4-hydroxyphenyl isopropyl)phenol, 2,6-bis(2-hydroxy-5′-methylbenzyl)-4-methylphenol, 2-(4-hydroxyphenyl)-2-(2,4-dihydroxyphenyl)propane, tetra(4-hydroxyphenyl)methane, tetra(4-(4-hydroxyphenyl isopropyl)phenoxy)methane, and 1,4-bis((4′,4″-dihydroxytriphenyl)methyl)benzene and 3,3-bis(3-methyl-4-hydroxyphenyl)-2-oxo-2,3-dihydroindole.

[0065] The amount of any branching agent used is from 0.05 mol% to 2.00 mol% based on the number of moles of the dihydroxyaryl compound used in each case.

[0066] The branching agent can be loaded first in an alkaline aqueous phase along with the dihydroxyaryl compound and chain terminator before phosgenation, or added dissolved in an organic solvent. In the case of transesterification, the branching agent is used together with the dihydroxyaryl compound.

[0067] Advantageously, the aromatic polycarbonate is based on bisphenol A and preferably has a thickness of 5.5 to 15 cm. 3 A melt volumetric flow rate (MVR) of 6 to 12 cm / min is preferred. 3 A melt volumetric flow rate (MVR) of 8 to 11 cm / min is preferred. 3 The melt volumetric flow rate (MVR) was measured per 10 min according to DIN EN ISO 1133-1:2012-03 (test temperature 300°C, mass 1.2 kg).

[0068] Preferably, the aromatic polycarbonate has a weight-average molecular weight (M0) of 20,000 to 32,000 g / mol, more preferably 23,000 to 28,000 g / mol, and even more preferably 24,000 to 26,000 g / mol. wThe chromatogram was determined by GPC (gel permeation chromatography) using bisphenol A-based polycarbonate as a standard.

[0069] As an example of an aromatic polycarbonate suitable for use in this invention, one could mention an example made from bisphenol A and phosgene and marketed by Covestro Co., Ltd. under the trade name... 2400 2600 2800 Those sold for 3100.

[0070] Aromatic polycarbonates can be used alone or in any desired mixture.

[0071] Advantageously, based on a total amount of 100 parts by weight of polycarbonate composition, aromatic polycarbonate is present in the polycarbonate composition in an amount of 80 to 97.5 parts by weight, preferably 90 to 97 parts by weight, more preferably 92 to 96.5 parts by weight, in any case, its amount together with other components to obtain a total amount of 100 parts by weight.

[0072] Component B

[0073] The polycarbonate composition according to the present invention comprises an organometallic sulfonate as component B.

[0074] The incorporation of organometallic sulfonates improves the flame retardancy of the polycarbonate compositions of the present invention.

[0075] Examples of metals contained in organometallic sulfonates include alkali metals such as lithium (Li), sodium (Na), potassium (K), rubidium (Rb), and cesium (Cs); alkaline earth metals such as magnesium (Mg), calcium (Ca), strontium (Sr), and barium (Ba); and aluminum (Al), titanium (Ti), iron (Fe), cobalt (Co), nickel (Ni), copper (Cu), zinc (Zn), zirconium (Zr), and molybdenum (Mo). Alkali metals or alkaline earth metals are preferred. The mechanical properties of polycarbonate resin, such as impact resistance, heat resistance, and good electrical properties, are not negatively affected by the addition of such flame-retardant salts. More preferably, the contained organometallic sulfonate is at least one metal salt compound selected from alkali metal salts and alkaline earth metal salts, and even more preferably, an alkali metal salt, wherein the metal is preferably sodium, potassium, or cesium. Examples of organometallic sulfonates include lithium (Li) organosulfonates, sodium (Na) organosulfonates, potassium (K) organosulfonates, rubidium (Rb) organosulfonates, cesium (Cs) organosulfonates, magnesium (Mg) organosulfonates, calcium (Ca) organosulfonates, strontium (Sr) organosulfonates, and barium (Ba) organosulfonates. Alkali metal organosulfonates are particularly preferred, including sodium (Na) organosulfonates, potassium (K) organosulfonate compounds, and cesium (Cs) organosulfonate compounds.

[0076] Preferred examples of organometallic sulfonates include metal salts of fluorinated aliphatic sulfonic acids, metal salts of fluorinated aliphatic sulfonamides, metal salts of aromatic sulfonic acids, and metal salts of aromatic sulfonamides.

[0077] Specific examples of those that are preferred include:

[0078] i) Metal salts of fluorinated aliphatic sulfonic acids, such as:

[0079] Alkali metal salts of fluorinated aliphatic sulfonic acids having at least one CF bond in the molecule, such as potassium perfluorobutyl sulfonate, lithium perfluorobutyl sulfonate, sodium perfluorobutyl sulfonate, cesium perfluorobutyl sulfonate, lithium trifluoromethanesulfonate, sodium trifluoromethanesulfonate, potassium trifluoromethanesulfonate, potassium trifluoroethanesulfonate, and potassium perfluoropropanesulfonate.

[0080] Alkaline earth metal salts of fluorinated aliphatic sulfonic acids having at least one CF bond in the molecule, such as magnesium perfluorobutyl sulfonate, calcium perfluorobutyl sulfonate, barium perfluorobutyl sulfonate, magnesium trifluoromethanesulfonate, calcium trifluoromethanesulfonate, and barium trifluoromethanesulfonate.

[0081] Alkali metal salts of fluorinated aliphatic disulfonic acids having at least one CF bond in the molecule, such as disodium perfluoromethane disulfonic acid, dipotassium perfluoromethane disulfonic acid, sodium perfluoroethane disulfonic acid, dipotassium perfluoroethane disulfonic acid, dipotassium perfluoropropane disulfonic acid, dipotassium perfluoroisopropane disulfonic acid, disodium perfluorobutane disulfonic acid, potassium perfluorobutane disulfonic acid, dipotassium perfluorobutane disulfonic acid, and dipotassium perfluorooctane disulfonic acid;

[0082] ii) Metal salts of fluorinated aliphatic sulfonamides, such as:

[0083] Alkali metal salts of fluorinated aliphatic disulfonyl imides having at least one CF bond in the molecule, such as lithium bis(perfluoropropanesulfonyl)imide, sodium bis(perfluoropropanesulfonyl)imide, potassium bis(perfluoropropanesulfonyl)imide, lithium bis(perfluorobutanesulfonyl)imide, sodium bis(perfluorobutanesulfonyl)imide, potassium bis(perfluorobutanesulfonyl)imide, potassium trifluoromethane (pentafluoroethane)sulfonylimide, sodium trifluoromethane (nonafluorobutane)sulfonylimide, potassium trifluoromethane (nonafluorobutane)sulfonylimide, trifluoromethane, etc.

[0084] Alkali metal salts of cyclic fluorinated aliphatic sulfonylimides having at least one CF bond in the molecule, such as lithium cyclohexafluoropropane-1,3-bis(sulfonyl)imide, sodium cyclohexafluoropropane-1,3-bis(sulfonyl)imide, and potassium cyclohexafluoropropane-1,3-bis(sulfonyl)imide.

[0085] iii) Metal salts of aromatic sulfonic acids, such as

[0086] Alkali metal salts of aromatic sulfonates having at least one aryl group in the molecule, such as dipotassium diphenyl sulfone-3,3′-disulfonate, potassium diphenyl sulfone-3-sulfonate, sodium benzenesulfonate, sodium (poly)styrenesulfonate, sodium p-toluenesulfonate, sodium (branched)dodecylbenzenesulfonate, sodium trichlorobenzenesulfonate, potassium benzenesulfonate, potassium styrenesulfonate, potassium (poly)styrenesulfonate, potassium p-toluenesulfonate, potassium (branched)dodecylbenzenesulfonate, potassium trichlorobenzenesulfonate, cesium benzenesulfonate, cesium (poly)styrenesulfonate, cesium p-toluenesulfonate, cesium (branched)dodecylbenzenesulfonate, and cesium trichlorobenzenesulfonate;

[0087] Alkaline earth metal salts of aromatic sulfonates having at least one aryl group in the molecule, such as magnesium p-toluenesulfonate, calcium p-toluenesulfonate, strontium p-toluenesulfonate, barium p-toluenesulfonate, magnesium (branched)dodecylbenzenesulfonate, and calcium (branched)dodecylbenzenesulfonate; and

[0088] iv) Metal salts of aromatic sulfonamides, such as:

[0089] Alkali metal salts of aromatic sulfonamides having at least one aryl group in the molecule, such as sodium salt of saccharin, potassium salt of N-(p-toluenesulfonyl)-p-toluenesulfonylimide, potassium salt of N-(N′-benzylaminocarbonyl)sulfanilimide, and potassium salt of N-(phenylcarboxyl)-sulfonamide.

[0090] More preferably are metal salts of fluorinated aliphatic sulfonic acids and metal salts of aromatic sulfonic acids, and particularly preferred are metal salts of fluorinated aliphatic sulfonic acids.

[0091] As metal salts of fluorinated aliphatic sulfonic acids, alkali metal salts of fluorinated aliphatic sulfonic acids having at least one CF bond in the molecule are preferred, and alkali metal salts of perfluoroalkane sulfonic acids are particularly preferred. Specifically, potassium perfluorobutylsulfonate is preferred. As metal salts of aromatic sulfonic acids, alkali metal salts of aromatic sulfonic acids are more preferred, and alkali metal salts of diphenyl sulfone sulfonic acids, such as dipotassium diphenyl sulfone-3,3′-disulfonate and potassium diphenyl sulfone-3-sulfonate, are particularly preferred; and alkali metal salts of p-toluenesulfonic acid, such as sodium p-toluenesulfonate, potassium p-toluenesulfonate, and cesium p-toluenesulfonate; and alkali metal salts of p-toluenesulfonic acid are even more preferred.

[0092] Meanwhile, organometallic sulfonates can be used in one type, or in any combination and proportion of two or more types.

[0093] In addition to the organometallic sulfonates mentioned above, polymer-type organometallic sulfonates may also be used as organometallic sulfonates for use in this invention. Examples of polymer-type organometallic sulfonates include metal salts having alkali metal sulfonate residues in thermoplastic resins such as polystyrene, polyacrylonitrile-styrene, polycarbonate, or polyethylene terephthalate.

[0094] As an example of a commercially available organometallic sulfonate, potassium perfluorobutyl sulfonate, sold by LANXESS AG Germany under the trade name Bayowet C4, can be mentioned. Potassium perfluorobutyl sulfonate is preferably used as component B.

[0095] Based on a total amount of 100 parts by weight of the polycarbonate composition, the organometallic sulfonate is present in the polycarbonate composition in an amount of 0.1 to 0.3 parts by weight, preferably 0.12 to 0.25 parts by weight, more preferably 0.15 to 0.2 parts by weight.

[0096] Component C

[0097] The polycarbonate composition according to the present invention comprises at least one anti-drip agent as component C.

[0098] Preferably, the at least one anti-dripping agent used is selected from fluorinated polyolefins.

[0099] Fluorinated polyolefins are known (see "Vinyl and Related Polymers", Schildknecht, John Wiley & Sons, Inc., New York, 1962, pp. 484-494; "Fluorpolymers", Wall, Wiley-Interscience, John Wiley & Sons, Inc., New York, Vol. 13, 1970, pp. 623-654; "Modern Plastics Encyclopedia", 1970-1971, Vol. 47, No. 10A, October 1970, McGraw-Hill, Inc., New York, pp. 134 and 774; "Modern Plastics Encyclopedia", 1975-1976, October 1975, Vol. 52, No. 10A, McGraw-Hill, Inc., New York, pp. 27, 28, and 472, and US-PS). 3 671 487, 3 723373 and 3 838 092).

[0100] Preferably, the anti-drip agent is selected from polytetrafluoroethylene, polyvinylidene fluoride, tetrafluoroethylene / hexafluoropropylene copolymer and ethylene / tetrafluoroethylene copolymer.

[0101] More preferably, polytetrafluoroethylene (PTFE) is used as an anti-drip agent.

[0102] Polytetrafluoroethylene (PTFE) can be produced by known methods, such as by incubating PTFE in an aqueous medium containing a free radical-forming catalyst, such as sodium peroxydisulfate, potassium peroxydisulfate, or ammonium peroxydisulfate, at a concentration of 7 to 71 kg / cm³. 2 Polymerization is carried out under pressure and at temperatures of 0 to 200°C, preferably at temperatures of 20 to 100°C. For further details, see, for example, U.S. Patent Application 2,393,967 A.

[0103] Preferably, the fluorinated polyolefin has a glass transition temperature exceeding -30°C, typically exceeding 100°C, a fluorine content preferably of 65 to 76% by weight, particularly 70 to 76% by weight (based on 100% by weight of the fluorinated polyolefin), and an average particle size d of 0.05 to 1,000 μm, preferably 0.08 to 20 μm. 50 .

[0104] For the purposes of this invention, the particle size d 50 The average value refers to a particle size such that 50% by weight of the relevant material has a larger particle size than the average value, and 50% by weight has a smaller particle size than the average value.

[0105] The d of the particles in the composition of the present invention 50 Average particle size can be determined by methods known to those skilled in the art, such as the d-value of PTFE polymer particles. 50 The value is obtained by using the appropriate equipment (e.g., from Malvern, for example). Micro or 3000) or Coulter (e.g., LS) Light scattering techniques (dynamic or laser) are used for measurement, particularly as described in methods ISO 13320-1, EP 1279694 A, and WO 2014 / 037375. Laser scattering based on light diffraction on particles is a suitable technique applicable to such powders for determining particle size distribution. In particular, it can be used for dry powders (e.g., using Coulter LS). (instrument) or for powders suspended in an aqueous solution of a suitable dispersant (a suitable apparatus is the Coulter LS) This analysis was performed.

[0106] Preferably, the fluorinated polyolefin has a content of 1.2 to 2.3 g / cm³ as measured according to ASTM D1895:2017. 3 The density.

[0107] More preferably, the fluorinated polyolefin used according to the present invention has an average particle size of 0.05 to 20 μm, preferably 0.08 to 10 μm, and a particle size distribution of 1.2 to 1.9 g / cm³. 3 The density.

[0108] Suitable fluorinated polyolefins that can be used in powder form have an average particle size of 100 to 1000 μm and a particle size of 2.0 g / cm³. 3 Up to 2.3 g / cm 3 A tetrafluoroethylene polymer with a density of [missing information].

[0109] As an example of a product containing polytetrafluoroethylene, DuPont can be mentioned under the trade name... Those that were sold.

[0110] Alternatively, masterbatches of polytetrafluoroethylene and styrene-acrylonitrile (SAN) in a 1:1 weight ratio can be used, such as ADS 5000 available from Chemical Innovation Co., Ltd and POLYB FS-200 available from Han Nanotech Co., Ltd.

[0111] Advantageously, based on a total amount of 100 parts by weight of the polycarbonate composition, the anti-drip agent is present in the polycarbonate composition according to the invention in an amount of 0.3 to 0.7 parts by weight, preferably 0.4 to 0.6 parts by weight.

[0112] Component D

[0113] The polycarbonate composition according to the present invention comprises at least one hydrolytic stabilizer as component D.

[0114] Hydrolytic stabilizers commonly used in polycarbonate compositions can be used in polycarbonate compositions according to the present invention.

[0115] For the purposes of this invention, the hydrolysis stabilizer is preferably selected from mineral clay and organic acids.

[0116] Examples of mineral clays include boehmite, gibbsite, diaspore, kaolinite (e.g., kaolinite, pyrophyllite), montmorillonite (e.g., montmorillonite, chlorodiaspore, soapstone), talc, etc.

[0117] Examples of organic acids include citric acid, phosphoric acid, and metaphosphoric acid.

[0118] Preferably, the hydrolysis stabilizer is selected from boehmite, kaolin, talc, citric acid, etc.

[0119] As a hydrolysis stabilizer, Sasol Germany GmbH can be mentioned under the trade name. Boehmite sold for 200, kaolin sold by KaMin LLC under the trade name Polyfil HG90, and IMIFABI SPA under the trade name Talc sold by Ultra 5C and citric acid sold by Weifang Ensign Industry Co., Ltd under the trade name Citric Acid Anhydrous.

[0120] If the hydrolytic stabilizer is boehmite, it is preferably present in the polycarbonate composition according to the invention in an amount of 0.2 to 2 parts by weight, based on a total amount of 100 parts by weight of the polycarbonate composition.

[0121] If the hydrolysis stabilizer is citric acid, it is preferably present in the polycarbonate composition according to the invention in an amount of 0.1 to 0.5 parts by weight, based on a total amount of 100 parts by weight of the polycarbonate composition.

[0122] If the hydrolysis stabilizer is kaolin, it is preferably present in the polycarbonate composition according to the invention in an amount of 1 to 4 parts by weight, based on a total amount of 100 parts by weight of the polycarbonate composition.

[0123] If the hydrolytic stabilizer is talc, it is preferably present in the polycarbonate composition according to the invention in an amount of 1 to 4 parts by weight, based on a total amount of 100 parts by weight of the polycarbonate composition.

[0124] Component E

[0125] The polycarbonate composition according to the present invention comprises at least one polysilsesquioxane as component E.

[0126] The polysilsesquioxane used in this article has properties derived from RSiO 1.5 The trifunctional siloxane unit (R is hydrogen or a monovalent organic group) (hereinafter referred to as "T unit") contains 90 mol% or more, more preferably 95 mol% or more, and even more preferably 100 mol% of the total siloxane units (M unit, D unit, T unit, Q unit) as 100 mol%.

[0127] Meanwhile, the M unit represents R3SiO 0.5 The unit represents a monofunctional siloxane unit (where R is hydrogen or a monovalent organic group), and the D unit represents a unit derived from R₂SiO₃. 1.0 The unit Q represents a difunctional siloxane unit (where R is hydrogen or a monovalent organic group), and the unit Q represents a siloxane unit derived from SiO₂. 2.0 The tetrafunctional siloxane unit is represented.

[0128] In addition to the T unit, the polysilsesquioxane may also contain the M unit.

[0129] Examples of R bonded to polysilsesquioxanes include hydrogen, C1-C... 12 Alkyl, C2-C 12 alkenyl, C1-C12 Alkoxy, C1-C 12 Acyl, C3-C8 cycloalkyl, and phenyl groups. Preferably, R is selected from hydrogen, C1-C6 alkyl, C1-C6 alkenyl, C1-C6 alkoxy, and phenyl. More preferably, R is selected from alkyl groups having 1 to 6 carbon atoms, such as methyl, ethyl, propyl, butyl, and hexyl. For the purposes of this invention, methyl is preferred as the organic group R. Preferably, polymethylsilsesquioxane is used alone or in combination with other polysilsesquioxanes as a polysilsesquioxane, and is particularly preferred when used alone.

[0130] The preferred polysilsesquioxanes described above can be prepared by publicly known methods. For example, as described in JP-A-01-217039, JP-A-5-125187, or JP-A-6-263875, polysilsesquioxanes are obtained by hydrolyzing an organosilane under acidic conditions, adding and mixing an aqueous alkali metal solution into an aqueous or aqueous / organic solvent of an organosilane triol, and keeping the product in a static state to thereby polycondense the organosilane triol.

[0131] Examples of commercial polysilsesquioxanes include polymethylsilsesquioxanes sold by GANZ CHEMICAL CO., LTD under the trade name Ganzpearl SI-020 and ABC NANOTECH CO., LTD under the trade name ABC E+308.

[0132] Based on a total amount of 100 parts by weight of the polycarbonate composition, the polysilsesquioxane is present in the polycarbonate composition according to the invention in an amount of 2 to 7, preferably 2.0 to 7.0, more preferably 3.0 to 5.0 parts by weight.

[0133] Component F

[0134] In addition to component AE mentioned above, the polycarbonate composition according to the invention may optionally contain one or more additional additives as component F in conventional amounts commonly used in polymer compositions. Such additives are lubricants, mold release agents (e.g., pentaerythritol tetrastearate (PETS), glyceryl monostearate (GMS), and their carbonates), antioxidants, dyes, pigments, ultraviolet absorbers, etc.

[0135] Those skilled in the art can select the type and amount of additional additives so as not to significantly and adversely affect the desired properties of the polycarbonate composition according to the invention. Based on a total polycarbonate composition of 100 parts by weight, the amount of additional additives is preferably up to 15 parts by weight, more preferably up to 10 parts by weight, and even more preferably up to 6 parts by weight.

[0136] Preferably, the polycarbonate composition according to the present invention comprises:

[0137] A) 80-97.35 parts by weight of an aromatic polycarbonate, wherein the aromatic polycarbonate is based on bisphenol A.

[0138] B) 0.15-0.25 parts by weight of an organometallic sulfonate, wherein the organometallic sulfonate contains at least potassium perfluorobutyl sulfonate as the organometallic sulfonate, more preferably potassium perfluorobutyl sulfonate.

[0139] C) 0.4-0.6 parts by weight of an anti-drip agent, wherein polytetrafluoroethylene is contained as an anti-drip agent, and more preferably, the anti-drip agent is polytetrafluoroethylene;

[0140] D) 0.1-4 parts by weight of hydrolytic stabilizer, wherein the hydrolytic stabilizer is selected from boehmite, kaolin, talc, citric acid, and combinations thereof, and

[0141] E) 2-7 parts by weight of polysilsesquioxane, wherein polymethylsilsesquioxane is contained as the polysilsesquioxane, more preferably, the polysilsesquioxane is polymethylsilsesquioxane.

[0142] The total amount of the composition is 100 parts by weight.

[0143] More preferably, the polycarbonate composition according to the present invention comprises the following:

[0144] A) 80-97.25 parts by weight of an aromatic polycarbonate, wherein the aromatic polycarbonate is based on bisphenol A.

[0145] B) 0.15-0.25 parts by weight of an organometallic sulfonate, wherein the organometallic sulfonate contains at least potassium perfluorobutyl sulfonate as the organometallic sulfonate, more preferably potassium perfluorobutyl sulfonate.

[0146] C) 0.4-0.6 parts by weight of an anti-drip agent, wherein polytetrafluoroethylene is contained as an anti-drip agent, and more preferably, the anti-drip agent is polytetrafluoroethylene;

[0147] D) 0.2-2 parts by weight of a hydrolysis stabilizer, wherein boehmite is contained as a hydrolysis stabilizer, and more preferably, the hydrolysis stabilizer is boehmite.

[0148] E) 2-7 parts by weight of polysilsesquioxane, wherein polymethylsilsesquioxane is contained as the polysilsesquioxane, more preferably, the polysilsesquioxane is polymethylsilsesquioxane, and

[0149] F) Up to 15 parts by weight of one or more additional additives selected from lubricants, mold release agents, antioxidants, dyes, pigments and UV absorbers.

[0150] The total amount of the composition is 100 parts by weight.

[0151] Or more preferably, the polycarbonate composition according to the present invention comprises the following:

[0152] A) 80-97.35 parts by weight of an aromatic polycarbonate, wherein the aromatic polycarbonate is based on bisphenol A.

[0153] B) 0.15-0.25 parts by weight of an organometallic sulfonate, wherein the organometallic sulfonate contains at least potassium perfluorobutyl sulfonate as an organometallic sulfonate, more preferably potassium perfluorobutyl sulfonate;

[0154] C) 0.4-0.6 parts by weight of an anti-drip agent, wherein polytetrafluoroethylene is contained as an anti-drip agent, and more preferably, the anti-drip agent is polytetrafluoroethylene;

[0155] D) 0.1-0.5 parts by weight of a hydrolysis stabilizer, wherein citric acid is contained as a hydrolysis stabilizer, preferably citric acid.

[0156] E) 2-5 parts by weight of polysilsesquioxane, wherein polymethylsilsesquioxane is contained as the polysilsesquioxane, more preferably, the polysilsesquioxane is polymethylsilsesquioxane.

[0157] F) Up to 15 parts by weight of one or more additional additives selected from lubricants, mold release agents, antioxidants, dyes, pigments and UV absorbers.

[0158] The total amount of the composition is 100 parts by weight.

[0159] Or more preferably, the polycarbonate composition according to the present invention comprises the following:

[0160] A) 80-96.45 parts by weight of an aromatic polycarbonate, wherein the aromatic polycarbonate is based on bisphenol A.

[0161] B) 0.15-0.25 parts by weight of an organometallic sulfonate, wherein the organometallic sulfonate contains at least potassium perfluorobutyl sulfonate as an organometallic sulfonate, more preferably potassium perfluorobutyl sulfonate;

[0162] C) 0.4-0.6 parts by weight of an anti-drip agent, wherein polytetrafluoroethylene is contained as an anti-drip agent, and more preferably, the anti-drip agent is polytetrafluoroethylene;

[0163] D) 1-4 parts by weight of a hydrolysis stabilizer, wherein the stabilizer contains kaolin as a hydrolysis stabilizer, preferably kaolin.

[0164] E) 2-4 parts by weight of polysilsesquioxane, wherein polymethylsilsesquioxane is contained as the polysilsesquioxane, more preferably, the polysilsesquioxane is polymethylsilsesquioxane, and

[0165] F) Up to 15 parts by weight of one or more additional additives selected from lubricants, mold release agents, antioxidants, dyes, pigments and UV absorbers.

[0166] The total amount of the composition is 100 parts by weight.

[0167] Or more preferably, the polycarbonate composition according to the present invention comprises the following:

[0168] A) 80-96.45 parts by weight of an aromatic polycarbonate, wherein the aromatic polycarbonate is based on bisphenol A.

[0169] B) 0.15-0.25 parts by weight of an organometallic sulfonate, wherein the organometallic sulfonate contains at least potassium perfluorobutyl sulfonate as an organometallic sulfonate, more preferably potassium perfluorobutyl sulfonate;

[0170] C) 0.4-0.6 parts by weight of an anti-drip agent, wherein polytetrafluoroethylene is contained as an anti-drip agent, and more preferably, the anti-drip agent is polytetrafluoroethylene;

[0171] D) 1-4 parts by weight of a hydrolysis stabilizer, wherein talc is contained as a hydrolysis stabilizer, preferably talc.

[0172] E) 2-4 parts by weight of polysilsesquioxane, wherein polymethylsilsesquioxane is contained as the polysilsesquioxane, more preferably, the polysilsesquioxane is polymethylsilsesquioxane, and

[0173] F) Up to 15 parts by weight of one or more additional additives selected from lubricants, mold release agents, antioxidants, dyes, pigments and UV absorbers.

[0174] The total amount of the composition is 100 parts by weight.

[0175] The inventors have discovered that the polycarbonate composition according to the present invention exhibits good flame retardancy even after immersion in hot water at 70°C for 7 days, and that articles made from this composition with a thickness of 1.2 mm can achieve V-0 performance before and after immersion in hot water at 70°C for 7 days.

[0176] Preparation of polycarbonate compositions

[0177] The polycarbonate composition according to the invention may be in, for example, pellet form, and may be prepared by various methods involving close mixing of the desired materials in the composition.

[0178] For example, the materials required in the composition are first blended in a high-speed mixer. Other low-shear methods, including but not limited to manual mixing, can also achieve this blending. The blend is then fed via a hopper into the throat of a twin-screw extruder. Alternatively, at least one component can be incorporated into the composition by being fed directly into the extruder at the throat and / or downstream via a side-filler. Additives can also be compounded with the desired polymer resin to form a masterbatch and fed into the extruder. The extruder is typically operated at a temperature higher than that required to cause the composition to flow. The extrudate is immediately quenched in a water bath and granulated. As described, the pellets can be 1 / 4 inch long or smaller. Such pellets can be used for subsequent molding, shaping, or forming.

[0179] Melt blending is the preferred method due to the availability of melt blending equipment in commercial polymer processing facilities.

[0180] Exemplary examples of equipment used in such melt processing methods include co-rotating and counter-rotating extruders, single-screw extruders, co-kneaders, and various other types of extrusion equipment.

[0181] The melt temperature during processing should preferably be minimized to avoid excessive degradation of the polymer. Ideally, the melt temperature in the molten resin composition should be maintained between 230°C and 350°C, although higher temperatures may be used as long as the residence time of the resin in the processing equipment remains short.

[0182] In some cases, the molten composition is discharged from processing equipment, such as an extruder, through a small outlet orifice in the die. The resulting filament is cooled by passing the molten resin through a water bath. The cooled filament can then be cut into pellets for packaging and further processing.

[0183] Molded products

[0184] The polycarbonate composition according to the invention can be used, for example, to produce various types of molded articles.

[0185] The present invention also provides molded articles made from polycarbonate compositions according to the present invention.

[0186] Examples of such molded articles include, for example, films; profiles; various housing components, such as those for household appliances like juicers, coffee makers, and blenders, or for office equipment like monitors, flat panel displays, laptops, printers, and copiers; sheets; tubing; electrical conduits; windows, doors, and other profiles for the construction industry (indoor and outdoor applications); electrical and electronic components such as switches, plugs, and sockets; and body parts or interior trim for commercial vehicles, especially for the motor vehicle industry.

[0187] Specifically, the molded article can be any of the following: interiors of rail vehicles, ships, airplanes, buses and other motor vehicles; housings of electrical equipment containing small transformers; housings of information processing and transmission equipment; housings and covers of medical equipment; housings of safety equipment; molded parts for sanitary and bathroom accessories; covering grilles for vents and housings of gardening tools; and battery packs.

[0188] Preparation of molded products

[0189] The polycarbonate composition according to the invention can be processed into molded articles by various means, such as injection molding, extrusion molding, blow molding or thermoforming.

[0190] The present invention provides a method for preparing molded articles made of compositions according to the present invention, comprising injection molding, extrusion molding, blow molding or thermoforming of polycarbonate compositions according to the present invention.

[0191] Uses of polysilsesquioxane

[0192] The inventors have unexpectedly discovered that polysilsesquioxanes can significantly improve the hydrolysis resistance of polycarbonate compositions containing hydrolysis stabilizers.

[0193] Therefore, the present invention provides the use of polysilsesquioxane as a hydrolysis resistance enhancer in a polycarbonate composition comprising at least one hydrolysis stabilizer, wherein the amount of polysilsesquioxane is 2-7 parts by weight based on a total amount of 100 parts by weight of the polycarbonate composition.

[0194] Preferably, the contained polysilsesquioxane has the composition of RSiO 1.5 The trifunctional siloxane unit (R is hydrogen or a monovalent organic group) (hereinafter referred to as "T unit") contains 90 mol% or more, more preferably 95 mol% or more, and even more preferably 100 mol% of the total siloxane units (M unit, D unit, T unit, Q unit) as 100 mol%.

[0195] Meanwhile, the M unit represents R3SiO 0.5 The unit represents a monofunctional siloxane unit (where R is hydrogen or a monovalent organic group), and the D unit represents a unit derived from R₂SiO₃. 1.0 The unit Q represents a difunctional siloxane unit (where R is hydrogen or a monovalent organic group), and the unit Q represents a siloxane unit derived from SiO₂. 2.0 The tetrafunctional siloxane unit is represented.

[0196] In addition to the T unit, the polysilsesquioxane may also contain the M unit.

[0197] Examples of R bonded to polysilsesquioxanes include hydrogen, C1-C... 12Alkyl, C2-C 12 alkenyl, C1-C 12 Alkoxy, C1-C 12 Acyl, C3-C8 cycloalkyl, and phenyl groups. Preferably, R is selected from hydrogen, C1-C6 alkyl, C1-C6 alkenyl, C1-C6 alkoxy, and phenyl. More preferably, R is selected from alkyl groups having 1 to 6 carbon atoms, such as methyl, ethyl, propyl, butyl, and hexyl. For the purposes of this invention, methyl is preferred as the organic group R. Preferably, polymethylsilsesquioxane is used as the polysilsesquioxane.

[0198] It is understood that the features mentioned as preferred, more preferred, etc., for polycarbonate compositions also apply to the use of polysilsesquioxanes according to the present invention.

[0199] The following examples illustrate the invention in more detail. Example

[0200] Materials used

[0201] Component A

[0202] A1: Has 12cm 3 Bisphenol A-based aromatic polycarbonate (PC) resins with a melt volume flow rate (MVR) of / 10 min (tested at 300 °C and 1.2 kg load according to DIN EN ISO 1133-1:2012-03) can be used as 2600 is from Covestro Polymer, Co., Ltd.

[0203] A2: Has 9.0cm 3 Bisphenol A-based aromatic polycarbonate (PC) resins with a melt volume flow rate (MVR) of / 10 min (tested at 300 °C and 1.2 kg load according to DIN EN ISO 1133-1:2012-03) can be used as 2800 was obtained from Covestro Polymer, Co., Ltd.

[0204] A3: Has 6.0cm 3 Bisphenol A-based aromatic polycarbonate (PC) resins with a melt volume flow rate (MVR) of / 10 min (tested at 300 °C and 1.2 kg load according to DIN EN ISO 1133-1:2012-03) can be used as 3100 is from Covestro Polymer, Co., Ltd.

[0205] Component B

[0206] B1: Potassium perfluorobutyl sulfonate, available as Bayowet C4 from LANXESS AG, Germany.

[0207] Component C

[0208] A masterbatch of polytetrafluoroethylene and styrene-acrylonitrile (SAN) in a C1:1:1 weight ratio is available as ADS 5000 from Chemical Innovation Co., Ltd., Thailand.

[0209] Component D

[0210] D1: Boehmite, can be used as... 200 from Sasol Germany GmbH

[0211] D2: Kaolin, available as Polyfil HG90 from KaMin LLC

[0212] D3: Talc, can be used as... Ultra 5C is from IMIFABI SPA

[0213] D4: Citric acid, available as anhydrous citric acid from Weifang EnsignIndustry Co., Ltd.

[0214] Component E

[0215] E1: Polymethylsilsesquioxane, with an average particle size of 0.8 ± 0.2 μm as determined by MALVERN MS2000, obtained from ABC NANOTECH CO., LTD. as ABC E+308.

[0216] E1: Polymethylsilsesquioxane, with an average particle size of 1.4-2.4 μm as determined by the Coulter Counter method, available as Ganzpearl SI-020 from GANZ CHEMICAL CO., LTD.

[0217] Component F

[0218] F1: Pentaerythritol tetrastearate (PETS), a mold release agent, available as Loxiol P 861 from EmeryOleochemicals Sdn Bhd Malaysia.

[0219] F2: 80% by weight 168 (tris(2,4-di-tert-butylphenyl) phosphite) and 20% by weight of 1076 (a mixture of 2,6-di-tert-butyl-4-(octadecyloxycarbonylethyl)phenol, which can be used as...) B900 is from BASF (China) Company Limited.

[0220] F3: Ultraviolet filter, 2,2′-methylenebis(6-(benzotriazol-2-yl)-4-tert-octylphenol, available as TINUVIN360 from BASF.

[0221] Test methods

[0222] The physical properties of the compositions according to the examples are tested as follows.

[0223] The notched impact strength of a cantilever beam is measured on a test bar with dimensions of 80 mm x 10 mm x 3 mm in accordance with ISO 180 / IA:2000.

[0224] Flame retardancy was evaluated on 127mm x 12.7mm x 1.2mm rods according to UL94-2015.

[0225] The hydrolytic stability of the prepared composition was assessed based on the change in flame retardancy rating measured on 127mm x 12.7mm x 1.2mm rods according to UL94:2015 before and after immersion in water at 70°C for 7 days.

[0226] Embodiments IE1-IE6 and Comparative Examples CE0-CE6 of this invention

[0227] The materials listed in Table 1 were compounded and granulated on a twin-screw extruder (ZSK-25) (Werner and Pfleider) at a rotational speed of 225 rpm, a throughput of 20 kg / h, and a machine temperature of 260°C. All parts by weight are calculated based on the weight of the active ingredient.

[0228] The granules are processed into corresponding samples on an injection molding machine at a melting temperature of 260°C and a mold temperature of 80°C.

[0229] The physical properties of the obtained compositions were tested, and the results are summarized in Table 1.

[0230] Table 1

[0231]

[0232] Failure*: means that V-1 was not passed.

[0233] The composition of Comparative Example 0 (CE0), which does not contain any hydrolytic stabilizer, exhibited a flame retardancy level of V-0 before immersion in water and a flame retardancy level of V-1 after immersion in water at 70°C for 7 days, indicating unacceptable hydrolysis resistance.

[0234] The compositions of Comparative Examples 1 to 4 (CE1-CE4) that do not contain any polysilsesquioxane exhibit a V-0 flame retardancy level before immersion in water, and fail to achieve a V-0 flame retardancy level after immersion in water at 70°C for 7 days, meaning that the hydrolysis resistance is unacceptable.

[0235] The comparison between Comparative Example 3 (CE3) and Comparative Example 4 (CE4) shows that even by significantly increasing the amount of hydrolytic stabilizer, it is impossible to achieve a V-0 flame retardant level after soaking in water at 70°C for 7 days.

[0236] Comparative examples CE0-CE4 show that hydrolysis resistance is unacceptable by simply adding hydrolysis stabilizers or polysilsesquioxanes.

[0237] Comparative Examples 5-6 (CE5-CE6), which contain all components AF and in which the amount of polysilsesquioxane based on a total of 100 parts by weight is no more than 1 part by weight, exhibited a flame retardancy level of V-0 before immersion in water and a flame retardancy level of V-1 after immersion in water at 70°C for 7 days, indicating unacceptable hydrolysis resistance.

[0238] The compositions of Examples 1-6 (IE1-IE6) of the present invention, which contain all components AF and wherein the amount of polysilsesquioxane is 2 to 7 parts by weight based on a total of 100 parts by weight of the composition, exhibit a flame retardancy level of V-0 before immersion in water and a flame retardancy level of V-0 after immersion in water at 70°C for 7 days, indicating excellent hydrolysis resistance.

[0239] Embodiments IE7-IE8 and Comparative Example CE7 of this invention

[0240] Similarly, the materials listed in Table 2 were mixed, the physical properties of the resulting compositions were tested, and the results are summarized in Table 2.

[0241] Table 2

[0242]

[0243] Failure*: means that V-1 was not passed.

[0244] The composition of Comparative Example 7 (CE7), which does not contain any polysilsesquioxane, exhibited a flame retardancy level of V-0 before immersion in water and failed to achieve a flame retardancy level of V-1 after immersion in water at 70°C for 7 days, meaning that its hydrolysis resistance was unacceptable.

[0245] The compositions of Examples 7-8 (IE7-IE8) of the present invention, which contain all components AF and wherein the amount of polysilsesquioxane is 3 parts by weight based on a total of 100 parts by weight of the composition, exhibit a flame retardancy level of V-0 before immersion in water and a flame retardancy level of V-0 after immersion in water at 70°C for 7 days, indicating excellent hydrolysis resistance.

[0246] Embodiments IE9-IE10 and Comparative Example CE8 of this invention

[0247] Similarly, the materials listed in Table 3 were mixed, the physical properties of the resulting compositions were tested, and the results are summarized in Table 3.

[0248] Table 3

[0249]

[0250] Failure*: means that V-1 was not passed.

[0251] The composition of Comparative Example CE8, which does not contain any polysilsesquioxane, exhibited a flame retardancy level of V-0 before immersion in water and failed to achieve a flame retardancy level of V-1 after immersion in water at 70°C for 7 days, meaning that its hydrolysis resistance was unacceptable.

[0252] The compositions of Examples IE9 and IE10 of the present invention, which contain all components AF and wherein the amount of polysilsesquioxane is 3 parts by weight based on a total of 100 parts by weight of the composition, exhibit a flame retardancy level of V-0 before immersion in water and a flame retardancy level of V-0 after immersion in water at 70°C for 7 days, indicating excellent hydrolysis resistance.

[0253] Embodiments IE11 and IE12 of the present invention and Comparative Example CE9

[0254] Similarly, the materials listed in Table 4 were mixed, the physical properties of the resulting compositions were tested, and the results are summarized in Table 4.

[0255] Table 4

[0256]

[0257] The composition of Comparative Example CE9, which does not contain any polysilsesquioxane, exhibited a flame retardancy level of V-0 before immersion in water and failed to achieve a flame retardancy level of V-1 after immersion in water at 70°C for 7 days, meaning that its hydrolysis resistance was unacceptable.

[0258] The compositions of Examples IE11 and IE12 of the present invention, which contain all components AF and wherein the amount of polysilsesquioxane is 3 parts by weight based on a total of 100 parts by weight of the composition, exhibit a flame retardancy level of V-0 before immersion in water and a flame retardancy level of V-0 after immersion in water at 70°C for 7 days, indicating excellent hydrolysis resistance.

[0259] Embodiments of the present invention IE13-IE20

[0260] Similarly, the materials listed in Table 5 were mixed, the physical properties of the resulting compositions were tested, and the results are summarized in Table 5.

[0261] Table 5

[0262]

[0263] The compositions of Examples IE13 to IE20 of the present invention, which contain all components AF and wherein the amount of polysilsesquioxane is 3.0 to 5.0 parts by weight based on a total of 100 parts by weight of the composition, exhibit a flame retardancy level of V-0 before immersion in water and a flame retardancy level of V-0 after immersion in water at 70°C for 7 days, indicating excellent hydrolysis resistance.

[0264] Furthermore, the compositions of embodiments IE13 to IE20 of the present invention exhibit good impact resistance even at lower temperatures of -30°C.

[0265] From the embodiments of the present invention described above, it can be concluded that the composition according to the present invention has a combination of hydrolysis resistance, flame retardancy, and good impact resistance even at low temperatures.

Claims

1. A polycarbonate composition comprising: A) 80-97.5 parts by weight of aromatic polycarbonate, B) 0.1-0.3 parts by weight of organometallic sulfonates; C) 0.3-0.7 parts by weight of anti-drip agent; D) 0.1-4 parts by weight of hydrolysis stabilizer, selected from boehmite, kaolin, talc, citric acid, and combinations thereof, and E) 2-7 parts by weight of polysilsesquioxane, The total amount of the composition is 100 parts by weight.

2. The composition according to claim 1, wherein the metal of the organometallic sulfonate is selected from one or more of the following: lithium (Li), sodium (Na), potassium (K), rubidium (Rb), cesium (Cs), magnesium (Mg), calcium (Ca), strontium (Sr), barium (Ba), aluminum (Al), titanium (Ti), iron (Fe), cobalt (Co), nickel (Ni), copper (Cu), zinc (Zn), zirconium (Zr), and molybdenum (Mo).

3. The composition according to claim 2, wherein the organometallic sulfonate is selected from metal salts of fluorinated aliphatic sulfonic acids, metal salts of fluorinated aliphatic sulfonamides, metal salts of aromatic sulfonic acids, metal salts of aromatic sulfonamides, and combinations thereof.

4. The composition according to claim 1, wherein the anti-drip agent is selected from fluorinated polyolefins, polyvinylidene fluoride, tetrafluoroethylene / hexafluoropropylene copolymers, ethylene / tetrafluoroethylene copolymers, and combinations thereof.

5. The composition according to claim 1, wherein the polysilsesquioxane has a composition of RSiO 1.5 The trifunctional siloxane unit is represented by R, which is hydrogen or a monovalent organic group, and contains 90 mol% or more of the unit based on 100% mol of total siloxane units.

6. The composition according to claim 5, wherein the organic group R is selected from hydrogen, C1-C64 ... 12 Alkyl, C2-C 12 alkenyl, C1-C 12 Alkoxy, C1-C 12 Acyl, C3-C8 cycloalkyl, hydroxyl and phenyl.

7. The composition according to claim 3, wherein the organometallic sulfonate is potassium perfluorobutyl sulfonate.

8. A molded article made from the composition according to any one of claims 1 to 7.

9. A method for preparing a molded article according to claim 8, comprising injection molding, extrusion molding, blow molding or thermoforming.

Citation Information

Patent Citations

  • Hydrolytically stable polycarbonates and processes for their production

    DE1570703A

  • Working up of additives in fat and protein - contng foodstuffs

    DE2036052A1

  • Saponification-resistant polycarbonates, processes for their production and their use

    DE2063050A1

  • PROCESS FOR THE MANUFACTURE OF SAPFONATION-STABLE BLOCKCOPOLYCARBONATES

    DE2211956A1

  • Process for preparing hydroxyaryloxy-terminated polydiorganosiloxanes

    DE3334782A1